Population Abundance and Density Estimates for Costa Rica’s Endemic Sea Snake, Hydrophis platurus xanthos - Bessesen, Brooke L.; Oedekoven, Cornelia S.; Galbreath, Gary J.; González-Suárez, Manuela (Frontiers in Marine Science, 2022)
Population abundance and density estimates provide key information for conservation assessment and prioritization of efforts and management. However, data are still largely unavailable for many taxa, including sea snakes, which appear to be facing global declines. Here, we present the first quantitative abundance and density estimates for the geographically isolated sea snake Hydrophis platurus xanthos endemic to the inner basin of Golfo Dulce, Costa Rica. Using systematic distance sampling methods, we obtained and analyzed 199 snake detections from 46 transect lines covering the entire known distribution (totaling nine days and 469 km of effort). Our modeling methods accounted for (i) the probability of detecting a snake given it was available to be detected (ii) the average availability of snakes at the water surface during a 24-hr cycle, and (iii) the by-hour variance in the taxon’s activity pattern. The best estimate of population abundance was 29781 individuals (95% CI=20104–44115) with an estimated density of 76 snakes/km2. Without historical abundance estimates or minimum viable population size, it is unknown whether this number represents a healthy population. However, with all individuals inhabiting a relatively small inlet increasingly exposed to anthropogenic impacts, the long-term persistence of H. p. xanthos may be threatened by ongoing impacts (boat propeller strikes, agricultural runoff, and climate change), as well as unforeseen events in the future.